Cross hepatotoxicity between tricyclic antidepressants. Issue 6 (June 1986) - Larrey, D; Rueff, B; Pessayre, D; Danan, G; Algard, M; Geneve, J; Benhamou, J P
Abstract : Cross hepatotoxicity between drugs in very uncommon. We report the case of a patient in whom acute hepatitis was induced by a tricyclic antidepressant, amineptine, and recurred early after administration of another tricyclic antidepressant, clomipramine. This observation suggests that the tricyclic ring is involved in the mechanism of the deleterious effect of both drugs to the liver.